XFEM based node scheme for the frictional contact crack problem. (15th April 2020) - Zhou, Xiao-Ping; Chen, Jun-Wei; Berto, Filippo
Highlights: The node-scheme method is firstly introduced into the XFEM to solve the frictional contact crack problems. The stress redistribution is considered in the local part of the crack surface in the proposed method. The proposed method has the ability to solve locking problems in the numerical simulation of the frictional contact crack. Abstract: In this paper, based on the nodal displacement of the crack surface element, a novel node-scheme method is proposed to model the frictional contact problem in the framework of extended finite element method (XFEM). The paper systematically illustrates the novel node-scheme including the fundamentals of the proposed method, the coupled Coulomb's friction model. The novelty of the proposed method is that the node-scheme method is first introduced into the XFEM, it can consider the stress redistribution in the local part of the crack surface, and it has the advantage of solving the locking phenomenon in the numerical simulation of the frictional contact problem. The numerical results show that the proposed method is accurate and applicable to efficiently solve the frictional contact crack problem.